2020
DOI: 10.1177/1078345820916240
|View full text |Cite
|
Sign up to set email alerts
|

Management and Complications of Non-Thumb Metacarpal Fractures in the Incarcerated Population

Abstract: We reviewed the patient demographics, injury mechanisms, fracture characteristics, treatment modalities, and outcomes of incarcerated patients who were referred for metacarpal fracture evaluation and treatment to our high-volume tertiary care center from a New York City Department of Correction infirmary facility. There is a scarcity of information in the orthopedic and plastic surgery literature on treating these common fractures in this vulnerable population. We conducted a basic statistical analysis and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Among the 12 studies with IRB approval, 6 included a waiver of consent, 13 , 20 24 while 6 did not report the status of consent waivers. 25 30 Four studies identified incarcerated patients through International Classification of Diseases (ICD) codes: Y92:14 X (prion as location of injury) or E849.7 (injury occurring in residential institution), 17 , 18 , 21 , 23 4 used admission or discharge locations, 16 , 23 , 27 , 28 8 used prison referral or electronic medical record review, 13 , 19 , 22 , 24 26 , 29 , 30 1 used prison billing data, 15 and 1 used prospective identification during consultation. 20 Using the ROBINS-E tool risk of bias assessment, 70.6% of the studies had high or very high concerns for bias (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 12 studies with IRB approval, 6 included a waiver of consent, 13 , 20 24 while 6 did not report the status of consent waivers. 25 30 Four studies identified incarcerated patients through International Classification of Diseases (ICD) codes: Y92:14 X (prion as location of injury) or E849.7 (injury occurring in residential institution), 17 , 18 , 21 , 23 4 used admission or discharge locations, 16 , 23 , 27 , 28 8 used prison referral or electronic medical record review, 13 , 19 , 22 , 24 26 , 29 , 30 1 used prison billing data, 15 and 1 used prospective identification during consultation. 20 Using the ROBINS-E tool risk of bias assessment, 70.6% of the studies had high or very high concerns for bias (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies reported on nonelective surgeries: 1 on emergency general surgery, 16 8 on trauma, 15 , 17 , 19 , 21 , 23 , 25 , 29 , 30 1 on both trauma and emergency general surgery 20 and 2 on burn surgery. 18 , 27 For emergency general surgery, 3 studies described conditions, 13 , 16 , 20 with only 1 comparing postoperative outcomes to nonincarcerated individuals (Supplemental Table 3, http://links.lww.com/AOSO/A345 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, the most common complication following the acute management of metacarpal fractures is stiffness. 18,19 Therefore, hand surgeons should be trying to reduce the extent and duration of immobilization so as to prevent soft tissue tightening while maintaining bony reduction.…”
Section: Discussionmentioning
confidence: 99%